Improving red cell transfusion in the elective surgical setting: an improvement collaborative with evaluation. Issue 4 (6th March 2015) - Harrison, B. T.; Chen, J.; Der Vartanian, C.; Isbister, J.; Tridgell, P.; Hughes, C. F.
<x xml:space="preserve">Abstract</x> Background & Objectives Significant research conducted in New South Wales (NSW) hospitals' indicated that about 30% of red cell transfusions in stable adult patients was inappropriate. Of the total Australian government blood product budget in 2009–2010 (i.e. 878·8 million dollars) was spent on fresh blood products and plasma collection. The Clinical Excellence Commission (CEC) launched a systematic intervention called Blood Watch (BW) aiming to reduce inappropriate red cell transfusions in all NSW hospitals. An evaluation of BW was undertaken to measure the effectiveness of the programme and to estimate the associated potential cost‐saving. Materials & Methods Through the deterministic linkage of the four population‐based administrative databases, three outcome indicators and four process indicators were developed. The analyses were of five elective surgical groups as they were the focus of the interventions. Three‐level logistic regression and three‐level linear regression were used to explore the time trend of the study process and outcome indicators. Modelling of the possible avoided red cell transfusions was also undertaken using a quadratic regression technique. Results Overall, there was a 27·4% reduction of the blood usage after the introduction of the BW programme and the reductions were consistent across five elective surgical groups. Such a reduction was associated with annual cost‐savings of over 8·5 million. Conclusions The BW programme which was based on collaborative improvement methods and implemented at scale led to significant reduction of blood usage, consistently across five elective surgical groups and significant cost‐saving.